Two-year follow-up study of elderly residents in S. Paulo, Brazil: methodology and preliminary results - Luiz R. Ramos; João Toniolo N.; Maysa S. Cendoroglo; Jacqueline T. Garcia; Myrian S. Najas; Monica Perracini; Cristina R. Paola; Fania C. Santos; Tereza Bilton; Simone J. Ebel; Maria B. M. Macedo; Clineu M. Almada F.; et al.
INTRODUCTION: Previous cross-sectional studies have shown a high prevalence of chronic disease and disability among the elderly. Given Brazil's rapid aging process and the obvious consequences of the growing number of old people with chronic diseases and associated disabilities for the provision of health services, a need was felt for a study that would overcome the limitations of cross-sectional data and shed some light on the main factors determining whether a person will live longer and free of disabling diseases, the so-called successful aging. The methodology of the first follow-up study of elderly residents in Brazil is presented. METHOD: The profile of the initial cohort is compared with previous cross-sectional data and an in-depth analysis of nonresponse is carried out in order to assess the validity of future longitudinal analysis. The EPIDOSO ('Epidemiologia do Idoso') Study conducted a two-year follow-up of 1,667 elderly people (65+), living in S. Paulo. The study consisted of two waves, each consisting of household, clinical, and biochemical surveys. RESULTS AND CONCLUSIONS: In general, the initial cohort showed a similar profile to previous cross-sectional samples in S. Paulo. There was a majority of women, mostly widows, living in multigenerational households, and a high prevalence of chronic illnesses, psychiatric disturbances, and physical disabilities. Despite all the difficulties inherent in follow-up studies, there was a fairly low rate of nonresponse to the household survey after two years, which did not actually affect the representation of the cohort at the final household assessment, making unbiased longitudinal analysis possible. Concerning the clinical and blood sampling surveys, the respondents tended to be younger and less disabled than the nonrespondents, limiting the use of the clinical and laboratory data to longitudinal analysis aimed at a healthier cohort. It is worth mentioning that gender, education, family support, and socioeconomic status were not important determinants of nonresponse, as is often the case.